A New Current Injection Based Power Flow Formulation. Issue 3 (7th February 2020) - Kumar, Abhishek; Jha, Bablesh Kumar; Singh, Devender; Misra, Rakesh Kumar
Abstract: This paper presents a novel current injection-based Newton-Raphson power flow algorithm with new PV bus representation ( rCINR − P V ) for improving the convergence characteristics. In this proposed algorithm, rectangular coordinates are used to represent all non-linear current injection equations. Test results are produced to discuss the reasons behind the non-convergence of different PV bus representation schemes, also their performance comparison was done on the unbalanced 3-phase radial (18-Bus, 28-Bus, 84- Bus and 140-Bus) and meshed (6-Bus, 14-Bus, 24-Bus, 30-Bus, 57-Bus, 118-Bus and 300-bus, and 1354-Bus) test systems. Experimental results show that the proposed power flow method provides better convergence property for distribution system with a large number of PV buses. Also, the modification leads to a smaller Jacobian matrix and therefore reduces computational time.